THE MODERNIZATION OF PESANTREN EDUCATION BASED ON NURCHOLIS MADJID'S PERSPECTIVES - Akhmad Miftakhul Mustofa (Tadibia Islamika, 2021)
Abstract This study aims to explore the world of Islamic boarding schools in the perspective of Nuschlish Madjid. Pesantren is not only an institution that only studies religious knowledge, but more than that, pesantren must also be able to answer the challenges of the times, so modernization is needed in it, especially in the digital era. The renewal of the pesantren was heavily influenced by the thoughts of several figures, one of which was Nurcholish Madjid. This research is a type of library research, with a historical-philosophical approach. The results of this study indicate that: 1) The institution of Islamic boarding schools underwent several changes, initially with a single leadership becoming a foundation. 2) The existing curriculum in Islamic boarding schools is undergoing modernization, the learning methods that were previously in the form of sorogan, lalaran, bandongan and halaqoh become a hierarchical method, the pesantren curriculum also includes additional lessons such as vocational (skills). 3) The function of the pesantren has been added, which initially served as the transmission and transfer of Islamic knowledge; maintenance of Islamic traditions; and reproduction of scholars; has now undergone a refunctionalization, namely venturing into social and economic functions so that it is able to keep up with the times.